Hubungan Interpersonal Pada Keluarga Campuran Muhammadiyah dan Nahdlatul Ulama di Desa Banjaranyar Lamongan - Zahroh, Fathimatuz; Hasanah, Eva Putriya (Universitas Nahdlatul Ulama Blitar, 2023)
This study aims to understand more deeply about the communication patterns of interpersonal relationship in a mixed fsmily of Muhammadiyah and NU in Banjaranyar village, Paciran sub-dstrict, Lamongan Regency. This study uses a qualitative descriptive method with interview and documentation data collection techniques. This study found that this mixed NU-Muhammadiyah family ran very harmoniously until the third generation of the family. From this, it was found that there are two patterns of communication that are carried out in maintaining interpersonal relationships in the family, these are: first, the level of conformity to the same values and held by each family member, namely mutual respect. This is reflected in the policy of family by parents to care for diversity and the cultivation of mutual acceptance through education and marriage. In addition, the value is also reflected in the practice of mutual respect between NU and Muhammadiyah. Second, the pattern of conversation in discussing something that focuses on making decisions based on deliberation. As well as intense commucation to discuss both online and offline